Estimating Effects of Temperature on Dengue Transmission in Colombian Cities (2017)
Dengue fever is a viral disease that affects tropical and subtropical regions of the world. It is well known that processes related to virus transmission by mosquitoes are highly influenced by weather. Temperature has been described as one of the climatic variables that largely governs the development and survival of mosquito eggs as well as the survival of all insect stages. Previously, we noted that high temperatures in the Colombian city of Riohacha negatively affect the establishment of dengue virus (DENV) infection in mosquitoes; in Bello and Villavicencio cities, which have lower average temperatures, DENV infection rates in mosquitoes are positively associated with a gradual increase in temperature. Here, we test the hypothesis that a similar effect of temperature can be detected in the incidence in the human population inhabiting dengue-endemic cities in Colombia.